Molecular and Computational Strategies to Increase the Efficiency of CRISPR-Based Techniques - Mattiello, Lucia; Rütgers, Mark; Sua-Rojas, Maria Fernanda; Tavares, Rafael; Soares, José Sérgio; Begcy, Kevin; Menossi, Marcelo (Frontiers in Plant Science, 2022)
The prokaryote-derived Clustered Regularly Interspaced Palindromic Repeats (CRISPR)/Cas mediated gene-editing tools have revolutionized our ability to precisely manipulate specific genome sequences in plants and animals. The simplicity, precision, affordability, and robustness of this technology have allowed a myriad of genomes from a diverse group of plant species to be successfully edited. Even though CRISPR/Cas, base editing, and prime editing technologies have been rapidly adopted and implemented in plants, their editing efficiency rate and specificity vary greatly. Here, we review the extensive literature on the recent advances on Cas9 and prime editing tools and their implications on enhancing editing efficiency. We also provide a perspective on the global future of agriculturally based products using DNA-free CRISPR/Cas techniques.